Economic Crisis and Convergence in the Eurozone Countries - Ferreiro, Jesús; Gálvez, Catalina; Gómez, Carmen; González, Ana (Panoeconomicus, 2017)
Although a key condition for the creation of a monetary union is the existence of similar structural characteristics that reduce the existence and incidence of asymmetric shocks, in the case of the Eurozone, most, if not all, studies have emphasized the existence of sizeable divergences both in the macroeconomic performances and in the structural elements of the Eurozone countries. The objective of the paper is to analyse whether the economic and financial crisis that is affecting the Eurozone since the year 2008 has had any impact of the coherence of the Eurozone, that is, whether after 2008 the differences in the macroeconomic performance of the euro counties are declining (convergence) or increasing (divergence). Key words: Economic crisis, Eurozone, Convergence, Sigma-convergence. JEL: F15, F45, O52. Iako slične strukturalne karakteristike koje smanjuju pojavu i učestalost asimetričnih šokova predstavljaju ključni uslov za stvaranje monetarne unije, u slučaju Evrozone, u većini studija, ako ne i svim, naglašava se postojanje značajne divergencije u makroekonomskim performansama i u strukturalnim elementima zemalja Evrozone. Rad ima za cilj da analizira da li je ekonomska i finansijska kriza koja pogađa Evrozonu od 2008. godine imala uticaja na koherentnost Evrozone, odnosno, da li nakon 2008. godine razlike u makroekonomskim performansama zemalja Evrozone opadaju (konvergencija) ili se povećavaju (divergencija). Ključne reči: Ekonomska kriza, Evrozona, konvergencija, sigma-konvergencija.